(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Using transnational settings as a lens, this research analyzes how South Asian diasporic narratives of the present day navigate the politics of home, belonging, and identity. The study examines literary works that deal with themes of cultural displacement, generational gaps, racialized experiences, and the emotional conflicts that arise from migration and remembrance. This piece delves into the ways in which authors use narrative techniques like fragmented storytelling, nostalgic memories, multilingual expression, and spatial symbolism to challenge rigid ideas of "home" and show how belonging is subject to constant change. Gender, class, nationalism, and cultural hybridity are just a few of the power dynamics illuminated by the study’s examination of postcolonial, feminist, and intersectional frameworks as they pertain to diaspora. In the end, this study contends that modern South Asian diasporic literature reimagines home as an ever-changing emotional and psychological terrain impacted by grief, longing, strength, and inventive rethinking, rather than a fixed location.